The Challenges of Millennial And Gen-Z Generation Workforce In Indonesia - Naam Fajar Basroni (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2023)
The intermediary role of HRD between employees and the company is crucial to satisfy both parties. As the workforce shifts from Baby Boomers and Gen-X to Millennials and Gen Z, companies must review their compensation and promotion systems to meet the new workforce's unique characteristics. This literature study examines the relationship between employee engagement and performance on the company's wage system and career opportunities. The study's practical goal is to provide a rationale for human resource development departments of businesses that will soon be hiring members of the Millennial and Gen-Z generations, outlining how corporate HRD systems might be revamped to accommodate the generational gap. Literature study allows us to explore various paradigms of these topics and to make new contributions to knowledge and understanding of issues. We concluded that companies must change the paradigm in the HRD system in dealing with the Millennial and Gen-Z generation workforce by naturally growing their engagement and performance and making the wage system and career promotion a reward for their efforts.